Risk of developing Type 2 Diabetes Mellitus in a vulnerable community in northern Argentina - ALEMAN, Mariano Nicolás; Luciardi, María Constanza; Medina , Mariana Soledad; Pera, Mariana; Centeno Maxzud, Mirta; Luciardi, Hector Lucas (Medicina Clínica y Social, 2024)
Introduction: Prevention of diabetes requires sustained lifestyle changes as well as identification of groups at higher risk. Objective: The aim of this research was to estimate the risk of diabetes in vulnerable subjects from a primary care center in northern Argentina, with no known glucose abnormalities, using the FINDRISC questionnaire, investigate the relationship between survey variables and the final score, and explore its association with metabolic risk factors and body composition. Methodology: This cross-sectional design included 498 patients without type 2 diabetes or known glycemic abnormalities. All subjects underwent a complete medical history and completed the FINDRISC questionnaire. Results: The predominant age group was 18-45 years old. Around 64% were physically active and 44% reported daily consumption of fruit and vegetables. Most of them had a BMI higher than 25 kg/m2. Regarding the risk of developing type 2 diabetes in the next 10 years, 24.3% were at low risk and the remaining fraction was distributed in slightly elevated, moderate, high and very high risk. All variables influenced the individuals' variance (p < 0.05). The hierarchical clustering and principal component analysis (PCA) revealed that elevated FINDRISC score was strongly associated with: age > 65 years, fasting blood glucose, BMI ? 30 kg/m2 and antihypertensives use. CONCLUTION: We found a high percentage of obesity and overweight, as well as a high risk of cardiometabolic disease and of developing T2D.  In addition, in the population studied, the variables that compose the FINDRISC did not influence the highest score in the same way.
Keywords: Diabetes mellitus, Type 2; Body Weight Changes; surveys and questionnaires